Writing bodies and bodies of text: Thinking vulnerability through monsters. Issue 2 (24th December 2021) - Henriksen, Line; Kjær, Katrine Meldgaard; Blønd, Marie; Cohn, Marisa; Cakici, Baki; Douglas‐Jones, Rachel; Ferreira, Pedro; Feshak, Viktoriya; Gahoonia, Simy Kaur; Sandbukt, Sunniva
Abstract: In this article, we suggest approaching writing as a vulnerable practice marked by an unstable boundary between bodies: bodies of text and bodies of writers. We present an exercise‐method that we refer to as Monster Writing, which we have developed in order to engage with these instabilities as well as in order to address experiences of difficulty, anxiety and uncertainty in relation with the text and writing process. Though the writing process can at times be exciting and thrilling, and at other times perhaps a little tedious and mundane, for some it also presents (more than) occasional encounters with one's own insecurities, shame and doubt. We argue that this potentially more painful relationship between writer and text should be awarded more attention in scholarship on writing, and that a way of doing so is through the framework of feminist theory on vulnerability, embodiment, and the monstrous.